2002
DOI: 10.1038/sj.mp.4000960
|View full text |Cite
|
Sign up to set email alerts
|

Age and the relationship of dopamine D3, serotonin 2C and serotonin 2A receptor genes to abnormal involuntary movements in chronic schizophrenia

Abstract: trols was within Hardy-Weinberg equilibrium. Odds ratio (OD) and their 95% confidence intervals were calculated to evaluate effects of different genotypes. We found a difference in the frequency of A/G alleles between the total amount of patients studied and controls which comes close to statistical significance ( 2 = 3.440; P = 0.063). The genotype distributions differed significantly in patients with AD compared to the controls ( 2 = 8.68; P = 0.013). The frequency of individuals who carried two copies of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
14
0

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 18 publications
1
14
0
Order By: Relevance
“…Studies on 5-HT6 and 5-HTT polymorphisms failed to find any association. 205,251,252 Further studies investigating 5-HT 2C , 5-HT 2A and D 3 genotypes with age and disease phenotypes 249,250 provided significant associations confirming the involvement of dopamine and serotonin systems in susceptibility to TD.…”
Section: Prediction Of Side Effectsmentioning
confidence: 78%
“…Studies on 5-HT6 and 5-HTT polymorphisms failed to find any association. 205,251,252 Further studies investigating 5-HT 2C , 5-HT 2A and D 3 genotypes with age and disease phenotypes 249,250 provided significant associations confirming the involvement of dopamine and serotonin systems in susceptibility to TD.…”
Section: Prediction Of Side Effectsmentioning
confidence: 78%
“…Another possible explanation is that older patients will generally have been exposed to antipsychotic drugs for a longer period. However, Segman and Lerer (2002b) controlled for years of exposure and found that the age effect on the genetic associations that they observed remained significant. Of the four published studies on the relationship of HTR 2A T102C to TD, in the two that found an association the mean age of the subjects was >50 yr Tan et al, 2001) and in the two which did not find an association the mean age Figure 4.…”
Section: Age-related Association Of Htr 2a With Tdmentioning
confidence: 85%
“…Two studies found T102C and A-1438G to be in close linkage disequilibrium (LD), Segman et al (2001) but not Basile et al (2001) observing an association with TD. Segman and Lerer (2002b) found that the association of T102C with TD was demonstrable in older but not younger patients.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Basile et al 58 and Herken et al 59 were unable to replicate these findings and, therefore, the role of the T102C variant in the 5-HT2A gene cannot be unambiguously associated with the occurrence of TD. Segman et al, 60 however, could demonstrate by further analysis that the effect of 5-HT2A in TD is age related: The 5-HT2A variant seems to confer risk for TD in older patients (449 years) but not in younger patients, which may explain the inconsistent findings. Of note, the T102 C and the A-1438G variants were found to be in linkage disequilibrium in the studies of Segman et al 56 and Basile et al; 58 therefore, similar results with both variants were obtained.…”
Section: The Serotonergic Systemmentioning
confidence: 96%